Caring for Nature: From Fact to Value, from Respect to Reverence - Rolston, Holmes (Zygon, 2004)
Abstract. Despite the classical prohibition of moving from fact to value, encounter with the biodiversity and plenitude of being in evolutionary natural history moves us to respect life, even to reverence it. Darwinian accounts are value-laden and necessary for understanding life at the same time that Darwinian theory fails to provide sufficient cause for the historically developing diversity and increasing complexity on Earth. Earth is a providing ground; matter and energy on Earth support life, but distinctive to life is information coded in the genetic molecules that superintends this matter-energy. Life is generated and regenerated in struggle, persists in its perishing. Such life is also a gift; nature is grace. Biologists and theologians join in celebrating and conserving the genesis on Earth, awed in their encounter with this creativity that characterizes our home planet.